Biogeochemical sensor performance in the SOCCOM profiling float array. Issue 8 (18th August 2017) - Johnson, Kenneth S.; Plant, Joshua N.; Coletti, Luke J.; Jannasch, Hans W.; Sakamoto, Carole M.; Riser, Stephen C.; Swift, Dana D.; Williams, Nancy L.; Boss, Emmanuel; Haëntjens, Nils; Talley, Lynne D.; Sarmiento, Jorge L.
Abstract: The Southern Ocean Carbon and Climate Observations and Modeling (SOCCOM) program has begun deploying a large array of biogeochemical sensors on profiling floats in the Southern Ocean. As of February 2016, 86 floats have been deployed. Here the focus is on 56 floats with quality‐controlled and adjusted data that have been in the water at least 6 months. The floats carry oxygen, nitrate, pH, chlorophyll fluorescence, and optical backscatter sensors. The raw data generated by these sensors can suffer from inaccurate initial calibrations and from sensor drift over time. Procedures to correct the data are defined. The initial accuracy of the adjusted concentrations is assessed by comparing the corrected data to laboratory measurements made on samples collected by a hydrographic cast with a rosette sampler at the float deployment station. The long‐term accuracy of the corrected data is compared to the GLODAPv2 data set whenever a float made a profile within 20 km of a GLODAPv2 station. Based on these assessments, the fleet average oxygen data are accurate to 1 ± 1%, nitrate to within 0.5 ± 0.5 µmol kg −1, and pH to 0.005 ± 0.007, where the error limit is 1 standard deviation of the fleet data. The bio‐optical measurements of chlorophyll fluorescence and optical backscatter are used to estimate chlorophyll a and particulate organic carbon concentration. The particulate organic carbon concentrations inferred from optical backscatter appear accurate to with 35 mg C m −3 or 20%, whichever is larger. Factors affecting the accuracy of the estimated chlorophyll a concentrations are evaluated. Plain Language Summary: The ocean science community must move toward greater use of autonomous platforms and sensors if we are to extend our knowledge of the effects of climate driven change within the ocean. Essential to this shift in observing strategies is an understanding of the performance that can be obtained from biogeochemical sensors on platforms deployed for years and the procedures used to process data. This is the subject of the manuscript. We show the performance of oxygen, nitrate, pH, and bio‐optical sensors that have been deployed on robotic profiling floats in the Southern Ocean for time periods up to 32 months. Key Points: Biogeochemical sensors on profiling floats require careful adjustments for sensor calibration error and drift After adjustment, biogeochemical sensor data can approach the accuracy found in large data sets such as GLODAP Adjusted sensor data accuracy has relatively little degradation over the many years a profiling float operates